FAT-TISSUE INJECTION VERSUS GRAFT - EXPERIMENTAL-STUDY IN RABBITS - Viterbo, Fausto [UNESP]; Marques, M.; Valente, M. (Little Brown Co, 1994)
An experimental study of fat-tissue implants in the ears and frontal regions of rabbits was conducted, starting with blocks of tissue for surgical implantation or with multifragmented pieces for injection. The implants were observed from day 7 to month 12. Low integration levels were observed in all animals, except for 1 case that had 20% and 42% of integration, respectively, for the block grafts and for the injected multifragmented tissue.